A Computational Investigation of Electronic Structure and Optical Properties of AlCuO2 and AlCu0.96Fe0.04O2: A First Principle Approach - Islam, Md. Tawhidul; Kumer, Ajoy; Chakma, Unesco; Howlader, Debashis (Orbital: The Electronic Journal of Chemistry, 2021)
The synthesized compound AlCuO2 was established and structurally characterized as the semiconductor. It is noted that there are no available data for theoretical studies, as well as computational studies. For developing theoretical studies on AlCuO2, this study has been designed by computational tools. Applying computational approaches, the electronic structure and optical properties were calculated for the AlCuO2 molecule, and computational tools of the CASTAP code from material studio 8.0 were used in this investigation. First of all, the band gap was recorded by 1.81 eV through the Generalized Gradient Approximation (GGA) based on the Perdew Burke Ernzerhof (PBE), and the density of state and the partial density of state were simulated for evaluating the nature of 3s2, 3p1 orbital for Al, 3d10, 4s1 orbital for Cu, 3d6, 4s2 orbital for Fe and 2s2, 2p4 orbital for O atom of AlCuO2. The optical properties, for instance, absorption, reflection, refractive index, conductivity, dielectric function, and loss function, were calculated. To develop the conducting nature, 4% Fe atom was doped by replacing the Cu atom on AlCuO2. As a result, the band gap was found at 0.00 eV having molecular formulation as AlCu0.96Fe0.04O2, as well as the optical conductivity and optical absorption was soared comparing with parent AlCuO2. From the analysis of the band gap and optical properties in AlCu0.96Fe0.04O2, it can be established that the semiconductor, AlCuO2, has converted into a superconductor due to 4% Fe atom doping. DOI: http://dx.doi.org/10.17807/orbital.v13i1.1533